2015
DOI: 10.5007/1980-0037.2015v17n4p400
|View full text |Cite
|
Sign up to set email alerts
|

Análise da demanda fisiológica crônica de uma temporada anual de futebol

Abstract: Exercise intensity monitoring has been essential for the control and planning of sports training. Thus, the aim of the present study was to assess the chronic physiological demand of soccer players during an annual soccer season using blood biomarkers. Ten professional soccer players (21.2 ± 3.7 years) participated in this study. Blood samples were collected on the day before beginning of preseason (C1); at the end of preseason and beginning of competitive calendar (C2); and at the end of the competitive calen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
0
4
2
Order By: Relevance
“…This result was supported by a previous study that showed that no significant changes in the T/C ratio after intense pre-season traninig in soccer players [ 88 ], and non-athletic men [ 83 ]. Contrary to our findings, recent studies observed significant reductions in the T/C ratio in response to a high volume of training sessions [ 39 , 89 ], and a period of congested match play [ 86 , 89 ] in professional soccer players. Similarly, another study demonstrated that a decrease equal or higher than 30% in the T/C ratio reflected state of catabolism, which resulted in a prolonged recovery time, fatigue, and deterioration of competitive soccer performance [ 90 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result was supported by a previous study that showed that no significant changes in the T/C ratio after intense pre-season traninig in soccer players [ 88 ], and non-athletic men [ 83 ]. Contrary to our findings, recent studies observed significant reductions in the T/C ratio in response to a high volume of training sessions [ 39 , 89 ], and a period of congested match play [ 86 , 89 ] in professional soccer players. Similarly, another study demonstrated that a decrease equal or higher than 30% in the T/C ratio reflected state of catabolism, which resulted in a prolonged recovery time, fatigue, and deterioration of competitive soccer performance [ 90 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, another study demonstrated that a decrease equal or higher than 30% in the T/C ratio reflected state of catabolism, which resulted in a prolonged recovery time, fatigue, and deterioration of competitive soccer performance [ 90 ]. Additionally, our result was not similar to previous studies that reported that the T/C ratio increased significantly in team sports athletes after the pre-season period [ 81 , 84 , 85 , 89 ]. As in the present study, Botelho et al [ 88 ] stated that a significantly unchanged T/C ratio after the pre-season period was associated with a favorable response to the training load, and adequate coping with training stresses.…”
Section: Discussioncontrasting
confidence: 99%
“…The blood CK concentration found after the preseason indicates that the training imposed some muscular overload that led to a leakage of CK into the bloodstream (33). However, the CK concentration (239 U•L 21 ) was lower than that reported by previous studies (8,26), indicating a good muscular recovery of athletes in association with adaptations during the preseason TL. For male elite soccer players, for example, Lazarim et al ( 26) suggested a blood CK upper limit value of 975 U•L 21 as an indication of an increased risk of muscular injury.…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies involving female soccer players showed that subjects' HRV is related to both their TL (r 5 -0.85) and perceived fatigue (r 5 0.56) during weeks of varying TL (17). In addition, other studies have found that high-intensity training or competitive periods may lead to increased salivary cortisol (9,31) and CK (8,26), with mood states (9) and the testosterone/ cortisol ratio (T/C) (31) also improving, specifically among female athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%